RESULTS OF SURGICAL TREATMENT FOR HYPERTROPHIC PSEUDOARTHROSIS OF THE HUMERUS DIAPHYSIS - A.M. Dursunov; O.Sh. Ruziqulov (Journal of modern medicine, 2026)
Introduction. Diaphyseal fractures of the humerus, complicated by incorrect selection of osteosynthesis technique, insufficient consideration of clinical risk factors, violation of orthopedic regimen by the patient, etc., lead to significant changes not only in the segment but also in the function of the upper limb. In this regard, an important stage is not only the clinical and radiological assessment of the condition of the injured limb and the type of false joint, but also the assessment of the significance of risk factors presents in the patient, which must be taken into account at all stages of management: the preoperative preparation stage, planning and conducting surgical treatment, and subsequent rehabilitation.Objective. Improving the results of surgical treatment for patients with hypertrophic pseudoarthrosis of the humerus diaphysis based on analyzing factors that disrupted the healing of the previous fracture, assessing the clinical risk factors present in the patient, and improving treatment technology.Materials and methods. It was studied based on a retrospective analysis of the medical histories of 30 patients with fractures of the humerus diaphysis and a prospective controlled study of the same patients with acquired hypertrophic pseudoarthrosis. The features of traumatic injury and the localization of hypertrophic pseudoarthrosis in the diaphysis of the humerus, previous osteosynthesis of the fracture, cortical index and body mass index indicators in the main and comparison groups. A description of the proposed method is provided, the task of which is to increase the effectiveness of surgical treatment for patients with brachial arthrosis in conditions of impaired blood supply by restoring microcirculation from altered and healthy bone areas using own tissues.Results. When comparing the consolidation indicators of bone fragments after hypertrophic pseudoarthrosis of the false joint, the average healing time in the main group was 156.5±7.5 days, and in the comparison group, it was 181.5±9.4 days [p < 0.05]. Based on clinical and radiological indicators, the effectiveness of treatment results for patients with hypertrophic in the primary group: good results were 95%, satisfactory results were 5%, and in the comparison group: good results were 50%, satisfactory results were 20%, and unsatisfactory results were 30%.Conclusion. Analysis of the results showed that a technically correctly performed operation to treat brachial diaphysis pseudoarthrosis allows for the restoration of normal anatomical tissue proportions and function of the affected limb with minimal resection of bone fragments, maintaining a positive result throughout the entire observation period. Treatment results for brachial arthrosis depend on the patient's initial condition and the adequate choice of treatment tactics, taking all components into account.